Managing Chronic Obstructive Pulmonary Disease 2007
DOI: 10.1002/9780470697603.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life

Abstract: Many veterinarians recommend using a "Quality of Life Scale" to help pet caregivers assess their aging or terminally ill pet's condition. Having a semi-objective scale can help you when your pet is ill and you are confused or worried that you might not be thinking clearly enough to make a proper decision on your pet's behalf. Dr Alice Villalobos, a renowned veterinary oncologist, created a scale for assessing quality of life called the HHHHHMM Scale: Hurt, Hunger, Hydration, Hygiene, Happiness, Mobility and Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Energy conservation involves modifying an activity or the environment to decrease the level of energy required to complete a task. Pacing and energy conservation are also used for management of fatigue ( 73 ). A recent randomized controlled trial of a 2-week training programme involving energy conservation techniques (ECT) for COPD patients ( 74 ), demonstrated that after the programme there was lower level of desaturation and decrease in the metabolic equivalent of task (MET) while performing activities of daily living.…”
Section: Fatigue Management Strategiesmentioning
confidence: 99%
“…Energy conservation involves modifying an activity or the environment to decrease the level of energy required to complete a task. Pacing and energy conservation are also used for management of fatigue ( 73 ). A recent randomized controlled trial of a 2-week training programme involving energy conservation techniques (ECT) for COPD patients ( 74 ), demonstrated that after the programme there was lower level of desaturation and decrease in the metabolic equivalent of task (MET) while performing activities of daily living.…”
Section: Fatigue Management Strategiesmentioning
confidence: 99%